Thermal aggregation and gelation of soy globulin at neutral pH. (December 2016) - Chen, Nannan; Zhao, Mouming; Chassenieux, Christophe; Nicolai, Taco
Abstract: Aggregation of soy globulin was studied in salt free aqueous solution at neutral pH over a wide range of concentrations (0.3–90 g/L) and temperatures (50–95 °C). The structure of the aggregates that were formed during heating was characterized with light scattering. In all cases aggregates with the same self-similar structure were observed that were characterized by a fractal dimension df = 2.0. Dynamic light scattering showed that the aggregates were flexible. The aggregate size increased with heating time and the rate of growth was characterized by an Arrhenius temperature dependence up to 85 °C with Ea = 180 kJ/mol independent of the concentration. For a given temperature the aggregation rate increased very strongly with increasing concentration. Gels were formed at concentrations down to 50 g/L and at temperatures down to 50 °C. Graphical abstract: Highlights: Thermal aggregation of SPI leads to the self-similar aggregates. The aggregate structure is independent of temperature and concentration. Aggregation and gelation is characterized by an activation energy of 150 kJ/mol. The aggregation rate decreases sharply with decreasing concentration.